Cognitive disorders in amyotrophic lateral sclerosis - M. A. Kutlubaev; D. K. Areprintceva; E. V. Pervushina; L. V. Brylev (Неврология, нейропсихиатрия, психосоматика, 2023)
Cognitive disorders (CD) are observed in more than half of patients with amyotrophic lateral sclerosis (ALS), but rarely reach the degree of dementia. Currently, a classification of ALS has been proposed depending on the presence of cognitive and/or behavioral disorders. CD in ALS can be represented by speech fluency disorders, various aphasic disorders, disorders of regulatory functions, social cognitive functions, and verbal memory. The most diagnostically sensitive are special scales, such as the Edinburgh Cognitive and Behavioral Impairment Screening Scale for ALS. CD in ALS have a negative impact on the outcome of the disease and the quality of life of patients and their families. This issue requires further study.